شدت پسندی اور دہشت گردی کے خلاف پاکستانی قوانین: تاریخ و نتائج: Pakistani Laws on Extremism and Terrorism: History and Outcomes (Al-Qamar, 2019)
This article discusses the history of Pakistani laws about Extremism and terrorism. It concludes that a lot of legislation has been enacted in Pakistan in this regard; special courts have been set up; severe punishments have been announced for the perpetrators and the structure of terrorism has been claimed to be weakened, but in fact, due to poor strategy, with an attempt to control terrorism, innocent civilians have been facing manifold problems. Unrest, especially in religious circles, has been erupted. The study suggests that an effective legislation as well as monitoring of law enforcement officials is urgently needed to properly address the problem. The National Action Plan is undoubtedly the most important document of national security. If this was fully implemented, terrorism and extremism could have been completely eradicated.
Keywords: Terrorism; extremism; legislation; Pakistan